THE POLICY OF POVERTY REDUCTION IN THE NATIONAL ECONOMY AND ITS SOCIO-ECONOMIC MECHANISMS (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article analyzes the innovative approaches to ensuring employment in the process of developing private entrepreneurship in the Republic of Uzbekistan. It explores new opportunities in areas such as the digital economy, remote jobs, startups, and technoparks, as well as the green economy and ecological entrepreneurship and the service sector. The article discusses methods of creating new jobs through the implementation of innovative technologies, vocational training, and retraining programs, and the ways to achieve economic diversification and sustainable development. The article highlights the importance of innovative approaches in addressing issues of entrepreneurship and employment in the country.